Measurement of Drug‐Stabilized Topoisomerase II Cleavage Complexes by Flow Cytometry. Issue 1 (5th July 2017) - de Campos Nebel, Marcelo; Palmitelli, Micaela; González‐Cid, Marcela
Abstract: The poisoning of Topoisomerase II (Top2) has been found to be useful as a therapeutic strategy for the treatment of several tumors. The mechanism of Top2 poisons involves a drug‐mediated stabilization of a Top2‐DNA complex, termed Top2 cleavage complex (Top2cc), which maintains a 5′ end of DNA covalently bound to a tyrosine from Top2 through a phosphodiester group. Drug‐stabilized Top2cc leads to Top2‐linked‐DNA breaks, which are believed to mediate their cytotoxicity. Several time‐consuming or cell type‐limiting assays have been used in the past to study drug‐stabilized Top2cc. Here, we describe a flow cytometry‐based method that allows a rapid assessment of drug‐induced Top2cc, which is suitable for high throughput analysis in almost any kind of human cell. The analyses of the drug‐induced Top2cc in the cell cycle context and the possibility to track its removal are additional benefits from this methodology. © 2017 by John Wiley & Sons, Inc.